DROPSHIPPING IN ONLINE GAMIS SALES: AN ANALYSIS THROUGH THE LENS OF SALAM CONTRACT PRINCIPLES - Angraini, Dewi Manda (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2025)
Dropshipping is a modern business method that allows sellers (dropshippers) to sell products without having direct stock of the items. In practice, dropshippers only utilize product images and descriptions from suppliers, then forward customer orders to the suppliers for product delivery. This study aims to analyze the mechanism of dropshipping in the online sale of gamis clothing and its compliance with the akad salam in the perspective of Islam. This research uses a qualitative approach with a literature review method to examine the concepts of dropshipping and akad salam. Based on the study results, dropshipping can be implemented in a Sharia-compliant manner under certain conditions, such as the clarity of contracts between dropshippers, suppliers, and customers; detailed product descriptions; and transparent collaboration. Furthermore, the application of akad salam in e-commerce can provide a solution for SMEs to empower the economy without reliance on interest-based debt, while maintaining honesty in business practices. By meeting Sharia requirements, dropshipping has significant potential to become a modern business alternative that not only fulfills market demands but also adheres to the principles of Islamic economics. A Sharia-compliant dropshipping system can support the development of online businesses with a foundation of integrity and sustainability. Keywords: dropshipping; akad salam, e-commerce; Islamic perspective